MANAJEMEN PENYELESAIAN PEMBIAYAAN BERMASALAH PADA LEMBAGA PERBANKAN SYARIAH - Muhamad Turmudi (Institut Agama Islam Negeri Kendari, 2016)
Abstract Islamic financing products divided into three categories; (1) financing using the principle of trading is distinguished by a form of payment and delivery time of goods. Products related to the sale and purchase agreement is financing murabaha, salam and istishna (2) financing lease using the principle is implemented in form ijaroh and ijaroh muntahiya bittamlik (3)financing using profit sharing principle is implemented in form of financing and Musharaka. Bank Indonesia Regulation No.7/2/PBI/2005 classify the credit quality assessment become current, special mention, substandard, doubtful and jammed. Financing is a product that has a high risk level, as to prevent any risk of financing can apply the standards of risk control and analyze carakter, capacity, capital, collateral, condition, sharia or analysts personalty, party, perpose, prosfect , payment, profitability, protection before realizing financing. In the event of any financing problems, the remedies can be done in the form of restructuring, settlement through a guarantee or write off. Keywords: Islamic finance, control and prevention of financial risks, efforts to resolve the financing problems.